Composite iron oxide–Prussian blue nanoparticles for magnetically guided T1-weighted magnetic resonance imaging and photothermal therapy of tumors - Kale SS (Dove Medical Press, 2017)
Shraddha S Kale,1,2 Rachel A Burga,1,3 Elizabeth E Sweeney,1 Zungho Zun,4–6 Raymond W Sze,1,4–6 Anthony Tuesca,7 J Anand Subramony,7 Rohan Fernandes1,3,5,61The Sheikh Zayed Institute for Pediatric Surgical Innovation, Children’s National Health System, Washington, DC, USA; 2Department of Biomedical Engineering, George Washington University, Washington, DC, USA; 3The Institute for Biomedical Sciences, George Washington University, Washington, DC, USA; 4Division of Diagnostic Imaging and Radiology, Children’s National Health System, Washington, DC, USA; 5Department of Radiology, George Washington University, Washington, DC, USA; 6Department of Pediatrics, George Washington University, Washington, DC, USA; 7MedImmune LLC, Gaithersburg, MD, USA Abstract: Theranostic nanoparticles offer the potential for mixing and matching disparate diagnostic and therapeutic functionalities within a single nanoparticle for the personalized treatment of diseases. In this article, we present composite iron oxide-gadolinium-containing Prussian blue nanoparticles (Fe3O4@GdPB) as a novel theranostic agent for T1-weighted magnetic resonance imaging (MRI) and photothermal therapy (PTT) of tumors. These particles combine the well-described properties and safety profiles of the constituent Fe3O4 nanoparticles and gadolinium-containing Prussian blue nanoparticles. The Fe3O4@GdPB nanoparticles function both as effective MRI contrast agents and PTT agents as determined by characterizing studies performed in vitro and retain their properties in the presence of cells. Importantly, the Fe3O4@GdPB nanoparticles function as effective MRI contrast agents in vivo by increasing signal:noise ratios in T1-weighted scans of tumors and as effective PTT agents in vivo by decreasing tumor growth rates and increasing survival in an animal model of neuroblastoma. These findings demonstrate the potential of the Fe3O4@GdPB nanoparticles to function as effective theranostic agents.Keywords: theranostics, Prussian blue, iron oxide, MRI, photothermal therapy, cancer